Regional growth management in the German metropolitan regions - Eichhorn, Sebastian; Diller, Christian; Pehlke, David (Raumforschung und Raumordnung | Spatial Research and Planning, 2022)
Metropolitan regions result from spatial rescaling processes and region formations and are considered as “soft spaces of governance”, referring to international debates on the “new regionalism”. This paper addresses the criticism that the focus on competitive metropolitan regions distracts from the need for action on classic spatial planning issues. For this, the paper examines and discusses the institutional integration of regional planning in the German metropolitan regions and the activities of regional growth management as well as the regulatory intensity of regional plans based on a group comparison of metropolitan regions. As a result, the thesis of an institutionally fragmented regulatory growth management by regional planning can only be confirmed for a few metropolitan regions, where no relevant institutions and instruments are implemented in the core area. Regarding the “soft” instruments of growth management, the situation is very different. Here, the action potential is not yet fully utilized, even in metropolitan regions with strong institutional cores
Keywords: Metropolitan regions; Urban development; Regional growth management; Management structures; Regulatory intensity